Pengaruh Motivasi Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Semen Padang - Yosefi Tiara Fitri; M. Afuan; Deni Saputra (Jurnal Ekonomi dan Bisnis Digital, 2026)
This research aims to find out and try to analyze the Influence of Work Motivation and Organizational Culture on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Semen Padang. This research is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of the Department Unit. Semen Padang as many as 50 people. The results of the study found that there is a significant influence of work motivation on job satisfaction, there is a significant influence of organizational culture on job satisfaction, there is no significant influence of work motivation on employee performance, there is a significant influence of organizational culture on employee performance, there is no significant influence of job satisfaction on employee performance, job satisfaction cannot mediate work motivation on employee performance, job satisfaction cannot mediate organizational culture on employee performance.